Wind farm output smoothing through coordinated control - Clemow,P; Green,TC (2010)
This paper presents a new method of using coordinated control and short term wind speed prediction to smooth the output of an array of wind turbines. The proposed controller uses knowledge of the kinetic energy storage potential in the rotor disc to allow production of pre-determined power profiles for periods of around 60s from variable wind inputs. Previous studies have shown that there are large peaks in wind power variability in the minutes timescale which is within the ability of a control system to reduce. This variation will cause issues with balancing systems within the local grid, as such it is beneficial to remove it. Results of tests to the system are presented which show a significant reduction in wind farm output power variability without a significant drop in output power. Comparisons with the natural smoothing effect are also presented and show that despite the significant smoothing found in large and distributed wind farms, there is still a possibility to improve the output.